Effects of irrigation methods on cucumber growth, yield and water use efficiency - DU She-ni; BAI Gang-shuan; LIANG Yin-li (浙江大学学报. 农业与生命科学版)
The effects of tradition irrigation, dropping irrigation, alternation irrigation and fixed irrigation on the growth, yield and water use efficiency of cucumber in sunlight greenhouse were analyzed. Results showed that the effects of four irrigation methods on plant height, stem diameter, leaf number and leaf area of cucumber were different. The prophase yield under different irrigation treatments were ranked in the descendant order of alternation irrigation, dropping irrigation, tradition irrigation, and fixed irrigation, and the metaphase, anaphase yield and total yield were ranked in the descendant order of dropping irrigation, alternation irrigation, fixed irrigation and tradition irrigation, respectively. Root activities of cucumber for dropping irrigation and alternation irrigation were remarkablely higher than those of tradition irrigation and fixed irrigation, but there was no significant difference between dropping irrigation and alternation irrigation. The order of water use efficiency and water output rate was as follows: dropping irrigation > alternation irrigation > fixed irrigation > tradition irrigation, however, the order of water consumption amount of cucumber was opposite. It is indicated that the suitable irrigation methods of cucumber are dropping irrigation and alternation irrigation in the sunlight greenhouse.